Taxonomic assignment of dietary arthropods in Malaysian swiftlets (Aerodramus sp.) based on DNA metabarcoding - Chan, Kok Sim; Tan, Ji; Goh, Wei Lim (The Journal of wildlife and parks, 2020)
Accuracy in species identification based on the DNA sequences is an important aspect of diet profiling. This study aims to compare the taxonomy assignment by BOLD Systems and BLAST for nucleotides (BLASTn) and to recommend general criteria that are crucial for taxonomic assignment in molecular identification of the dietary arthropods. We have obtained 27 DNA haplotypes of the partial mitochondrial cytochrome c oxidase I (COI) region for the dietary arthropods of house-farm swiftlets (Apodidae, Aerodramus). Searches were performed using the Barcodes of Life Data (BOLD) Systems (Public Record Barcode Database and All Barcode Record in BOLD) and Basic Local Alignment Search Tool for nucleotide (BLASTn) search. High level of “No match” cases (ca. 78%) in BOLD Systems and discrepancy cases in the search results based on different databases (ca. 22%) were observed in this study. We demonstrated how we had identified the COI sequences to specific-level (ca. 7%), generic-level (4%), familial-level (63%) or order-level (ca. 19%). We recommend three criteria that are crucial in molecular identification using a relatively short-length metabarcode sequence of the dietary arthropods: (1) the query sequence search should be performed in more than one database; (2) the query sequence and the sequences of its BLASTn top hit should be subject to phylogenetic analysis; and (3) identification at low taxonomic levels (genericand specific-levels) should be verified with the geographical distribution records